The Effect of Polymer Content on the Non-Newtonian Behavior of Acetaminophen Suspension. (10th September 2013) - Moghimipour, Eskandar; Kouchak, Maryam; Salimi, Anayatollah; Bahrampour, Saeed; Handali, Somayeh
Abstract : Acetaminophen is used as an analgesic and antipyretic agent. The aim of the study was evaluation of the effect of different polymers on rheological behavior of acetaminophen suspension. In order to achieve controlled flocculation, sodium chloride was added. Then structural vehicles such as carboxymethyl cellulose (CMC), polyvinyl pyrrolidone (PVP), tragacanth, and magnesium aluminum silicate (Veegum) were evaluated individually and in combination. Physical stability parameters such as sedimentation volume (F ), redispersibility (n ), and growth of crystals of the suspensions were determined. Also, the rheological properties of formulations were studied. The results of this study showed that the combination of suspending agents had the most physical stability and pseudoplastic behavior with some degree of thixotropy. Viscosity of suspensions was increased by adding NaCl 0.02%. Presence of PVP is necessary for improving rheological behavior of suspensions by NaCl. This may be related to the cross-linking between the carbonyl group in the PVP segment and Na + ions.